Thromboprophilaxis in neurological conditions in pregnancy. A clinical dilemma or a methods dilemma? - Parco, Sergio; Vascotto, Fulvia; Simeone, Roberto (Minerva Ginecol, 2016)

No evidence of Polyomavirus and EBV infections in Italian patients with mixed cryoglobulinemia infected chronically with HCV. - Comar, Manola; Zanotta, Nunzia; Del Savio, Rossella; Vascotto, Fulvia; Calabrese, Nadia; Zorat, Francesca; Pozzato, Gabriele (J Med Virol, 2014)
Mixed cryoglobulinemia is a lymphoproliferative disorder associated with hepatitis C virus (HCV). In patients chronically affected by HCV the prevalence of mixed cryoglobulinemia is variable ranging from 0% to 56%. To verify whether polyomaviruses (PyV) play a role in this disorder a total of 222 blood samples from 63 HCV chronic patients, 43 with mixed cryoglobulinemia, 59 chronic lymphocytic leukemia, 50 polytransfused patients, and 50 blood donors were evaluated for Merkel (MCPyV), BKV, JCV, and SV40. EBV was additionally included in the analysis since association with this disorder has been reported. Mixed cryoglobulinemia patients infected chronically with HCV resulted negative for both PyV and EBV. MCPyV was found in 1 subject with Merkel Cell Carcinoma, in 10% of polytransfused and in 10% of blood donors while EBV was detected in 22% of polytransfused, 10% of B-cell lymphatic leukemia patients and 4% of blood donors (P < 0.01). Taken together, the absence of PyV and EBV in HCV-mixed cryoglobulinemia patients seems to exclude a direct involvement of these viruses in the pathogenesis of this disease while the presence of MCPyV in healthy individuals, at the same rate as in polytransfused patients, may reinforce data on a minimal role of this virus in other human pathologies.
Keywords: Adult; Base Sequence; Cryoglobulinemia; DNA, Viral; Epstein-Barr Virus Infections; Female; Hepacivirus; Hepatitis C, Chronic; Herpesvirus 4, Human; Humans; Italy; Leukemia, B-Cell; Male; Middle Aged; Polyomavirus; Polyomavirus Infections; Sequence Analysis, DNA; Vaginal Smears; Young Adult

Application of reticulated platelets to transfusion management during autologous stem cell transplantation. - Parco, Sergio; Vascotto, Fulvia (Onco Targets Ther, 2012)
BACKGROUND: The immature (or reticulated) platelet fraction (IPF) is rich in nucleic acids, especially RNA, and can be used as a predictive factor for platelet recovery in platelet immunomediated consumption or in postchemotherapy myelosuppression. Our aim was to determine if transfusions with IPF-rich solutions, during autologous peripheral blood stem cell transplantation, reduce the occurrence of bleeding and hemorrhagic complications. PATIENTS AND METHODS: Transfusions were administered to 40 children, affected with hematological pathologies, who underwent autologous peripheral hematopoietic progenitor cell transplantation. There were two groups of 20 patients, one group treated with IPF-poor and the other with IPF-rich solutions. In the two groups, the conditioning regimen was the same for the same pathology (hematological pathologies: 14 acute lymphoblastic leukemia; twelve acute myelocytic leukemia; four non-Hodgkin's lymphoma; two Hodgkin's lymphoma; eight solid tumors). A new automated analyzer was used to quantify the IPF: the XE2100 (Sysmex, Kobe, Japan) blood cell counter with upgraded software. RESULTS: The 20 patients who received solutions with a high percentage of IPF (3%-9% of total number of infused platelets) required fewer transfusions than the 20 patients who received transfusions with a low percentage of IPF (0%-1% of total number of infused platelets): 83 versus 129 (mean of number of transfusions 4.15 versus 6.45) and a significant difference was found between the two groups by using the Mann-Whitney test (P < 0.001). The prophylactic transfusions decreased from three to two per week. There was only one case of massive hemorrhage. CONCLUSION: The use of IPF solutions reduces the number of transfusions and bleedings after peripheral blood stem cell transplantation in pediatric patients.

Autologous cord blood harvesting in North Eastern Italy: ethical questions and emerging hopes for curing diabetes and celiac disease. - Parco, Sergio; Vascotto, Fulvia (Int J Gen Med, 2012)
BACKGROUND: The Friuli Venezia Giulia (FVG), a region of North Eastern Italy, has passed legislation (Decree No 2324/2010) to regulate the banking of umbilical cord blood samples for personal, autologous, or family-directed use, and to implement the Agreement of the State-Regions Permanent Conference (Decree No 62/CSR/2010). This paper aims to identify the formalities and the reasons why families collect and bank their cord blood in foreign banks for both personal and private use. METHODS: To this end, at the Institute for Maternal and Child Health of Trieste (the regional capital city of the FVG), Italy, which assists about 1800 pregnant women a year, 129 questionnaires, drafted from January 2010 to December 2011 and concerning the granting of authorization to export samples, were examined. RESULTS: The collected data showed that 75% of involved families had resorted to anonymous public collection, which is available to anyone with therapeutic needs, and provided compatibility and hematologic protocols recognized by the scientific and international community (main indications: leukemia, hemoglobinopaties, and inherited hematologic and immunologic disorders). Conversely, 25.0% requested private storage at a foreign bank for personal or family-dedicated use. The principal motivation by disease was for treatment for diabetes (22.4%) and celiac disease (19.7%) (a multiorgan disease for which the FVG region has provided safeguards by approving a specific law granting support to families; Decree No 561/2007). For these two types of disease we found that information was received from the internet and not from general medical physicians, with a significant difference found using the χ(2) test (P < 0.01). CONCLUSION: The indication of treating these diseases with cord blood stem cell transplantation appears to be well grounded and encouraging, and has recently been corroborated by the international literature; however, the economic and social motivations promoting cord blood storage, for a fee, in the event of diseases that are still under study, require accurate information through general medical physicians on the actual possibilities of treatment.

Celiac disease and immigration in Northeastern Italy: the "drawn double nostalgia" of "cozonac" and "panettone" slices. - Parco, Sergio; Città, Angelo; Vascotto, Fulvia; Tamaro, Giorgio (Clin Exp Gastroenterol, 2011)
Many investigators consider children's drawings to be an important test in the evaluation of stress and anxiety, but few studies have examined the reliability and validity of indicators of emotional distress in children's projective drawings. In this report, we describe screening tests in children coming to the Friuli Venezia Giulia region in Northeastern Italy from non-European Union regions and suspected to have celiac disease, the problems involved in diagnosis of the disease, and the "drawn double nostalgia" of Romanian children for both Italian food and traditional Romanian foods. Of 3150 Western European cases, we found 712 with positive antibodies for IgA/IgG antitransglutaminase, 174 with a positive antiendomysium antibody confirmation test, and 20 with an IgA deficit. Of the children examined, 93% were children native to Western Europe, 4% were immigrants from Eastern Europe, and 1.6% originated from Africa. Among these, four Romanian children with celiac disease brought in their drawings, as requested in a hospital questionnaire. The prevalence of celiac disease is destined to increase among immigrants. Economic problems are common, and the twin nostalgia of immigrant children for foods and tastes that are "cozonac" (from the native country) and "panettone" (Italian cake flavor) represents a problem that will be difficult to resolve. Only some children's hospitals in Italy, ie, Burlo Garofolo and Gaslini, public and private foundations, or volunteer associations would be able to deal with this problem.

Serum anti-Müllerian hormone as a predictive marker of polycystic ovarian syndrome. - Parco, Sergio; Novelli, Caterina; Vascotto, Fulvia; Princi, Tanja (Int J Gen Med, 2011)
BACKGROUND: The anti-Müllerian hormone (AMH) is a dimeric protein secreted by the female ovaries and has two fundamental roles in follicle genesis. It delays the entrance of the primordial follicle into the pool of follicles in growth and diminishes the sensitivity of the ovarian follicle towards follicle-stimulating hormone (FSH). The purpose of this work was to study the AMH (nv 2.0-6.8 ng/mL) as a marker during assisted reproductive technology (ART), in order to identify cases of infertility due to polycystic ovarian syndrome (PCOS). This syndrome affects 10% of women with infertility problems, and a new biological marker could be useful to general practitioners of internal medicine to help generate the suspicion of PCOS so that they can refer the patient to the gynecologist for confirmation. METHODS: This study enrolled 236 patients aged 26-46 years undergoing assisted reproductive technology at the Institute for Maternal and Child Health, Trieste, Italy. On the third day of the ovarian cycle, the patients were given doses of AMH, FSH, and luteinizing hormone (LH, in cases of AMH < 2.0-6.8 ng/mL). A control pelvic ultrasound was also carried out. RESULTS: We identified 57 patients who were starting in vitro fertilization or embryo transfer with AMH values within the normal range (3.64 ± 1.51 ng/mL), 77 with values below normal (1.38 ± 0.32 ng/mL), and 96 cases with undetectable values of AMH. Six patients had very high AMH levels (10.0 ± 2.28 ng/mL) and, of these, five were found to have PCOS on pelvic ultrasound examination (P < 0.05). We also found inverse correlations between AMH levels and age (r = -0.52) and between AMH and FSH levels (r = -0.32). CONCLUSION: In clinical practice it is common to encounter patients who turn to medicine in search of a cure for female infertility. In our experience, AMH two or three times the normal amount (10 ± 2.28 ng/mL), is a good indication of PCOS and infertility.